Comércio Exterior Brasileiro e os Desafios da Interdependência Complexa: Brazilian Foreign Trade and the Challenges of Complex Interdependence - Schimanski, Silvana (2023)
The general objective of this paper is to present the profile of Brazilian foreign trade and its main challenges in a context of global interdependence. The economic globalization has deepened the interdependence between countries, consolidating international production chains and highlighting vulnerabilities in strategic sectors, such as services related to international maritime transport. The essay was prepared using a qualitative approach, based on secondary sources, and has an analytical-descriptive purpose. The Brazilian case suggests the country's vulnerability, not only because of its dependence on foreign companies to transport its foreign trade, but also due to the port services granted to international groups in the country's main terminals.